Educational Management in the System of Pupils’ Orientation to a Pedagogical Profession - Valentina I. Revyakina; Natalya V. Kharina; Vasilii Ya. Sinenko; Elena L. Rudneva; Albina A. Temerbekova; Anna R. Demchenko (International Review of Management and Marketing, 2016)
The relevance of the problem is determined by abrupt aggravating of a human recourses problem in a Russian comprehensive secondary school. The leading approaches used to solve this problem are strategic planning, management and coordination of collaboration and cooperation of municipal educational organizations putting into practice various types and forms of activities to train personnel reserve for education. The purpose of the given article is to show the outcomes of the experiment conducted in Tomsk State Pedagogical University (TSPU). This experiment enables the solution of the problem associated with the deficiency of school teachers in Tomsk Region through the creation and operation of a special system of two-year special-purpose (subject-oriented) pedagogical grades at a senior stage of a comprehensive secondary school. Pupils’ survey, diagnostics, research projects, analytic and prognostic debates, testing and business games were chosen as the leading techniques in the solution of the above specified problem. They allowed us to identify school leavers’ professional inclinations and their motivations in the pedagogical career choice. About 7 thousand senior high-school students and 326 school teachers participated in ten year experiment. School teaches fulfilled the role of managers, organizing and managing the pre-university training in the system of special-purpose (subject-oriented) pedagogical grades. Perspective forms of youth motivation strengthening to a pedagogical career choice were determined experimentally. The following motivations were chosen as leading: the compulsory foundation of a pedagogical-oriented grade at a senior stage; cooperative research activity of senior pupils and students from a pedagogical university; professional experiences of pupils studying in pedagogical grades as a facilitator (teaching assistant) at primary school and as a leader (counselor) in a summer school camp.